2007
DOI: 10.1111/j.1600-0765.2006.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐related parameters and periodontal conditions in children

Abstract: These findings suggest that accelerated periodontal destruction in young people with diabetes is related to the level of metabolic control. Good metabolic control may be important in addressing periodontal complications in young patients with diabetes, similarly to what is well established for other systemic complications of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 24 publications
2
63
1
5
Order By: Relevance
“…12,13 Scaling and root planing (SRP) therapy, in combination (or not) with antimicrobial agents, might be effective in reducing periodontal pathogens in persons with DM, 14,15 although others have reported that SRP alone may not be capable of eliminating or reducing Tannerella forsythia and Porphyromonas gingivalis in those individuals. 4,8,16,17,18 In general, a reduced level of those pathogens is crucial for a good response to therapy. 19,20 Analysis of data in the literature shows that it is unclear whether the subgingival microbiota in persons with DM is significantly affected by SRP.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Scaling and root planing (SRP) therapy, in combination (or not) with antimicrobial agents, might be effective in reducing periodontal pathogens in persons with DM, 14,15 although others have reported that SRP alone may not be capable of eliminating or reducing Tannerella forsythia and Porphyromonas gingivalis in those individuals. 4,8,16,17,18 In general, a reduced level of those pathogens is crucial for a good response to therapy. 19,20 Analysis of data in the literature shows that it is unclear whether the subgingival microbiota in persons with DM is significantly affected by SRP.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…2,3 Persons with poorly controlled DM also present more severe periodontal disease than do those with well-controlled DM. 4,5 Several mechanisms have been proposed to explain the periodontal etiopathogenesis in patients with DM. 3,6 Significant differences may be present in…”
mentioning
confidence: 99%
“…Mean Gi values in groups with "moderately poor" and "poor metabolic control" were higher comparing to the values in group with "good metabolic control" (p<0,05). Lalla E et al 24 measured attachment loss and gingival bleeding separately, and similarly as previous investigators noticed that HbA1c was positively and significantly correlated with gingival bleeding, but not with attachment loss alone 24,27 . Similar findings were noticed in the present investigation where mean Gi values in groups with "moderate poor" and "poor metabolic control" were higher comparing to group with "good metabolic control" (p<0,05).…”
Section: Discussionmentioning
confidence: 69%
“…The general opinion is that there is no effect of gender on elevated blood glucose in diabetic patients, as noticed in this study, whereas both sexes were uniformly represented 24 . Diabetic patients with poor metabolic control are at a high risk for a poor periodontal prognosis 7,8 .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation